2009
DOI: 10.15376/biores.4.4.1663-1669
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and dielectric properties of pine wood in the transverse direction

Abstract: In this paper, the thermal conductivity and dielectric parameters for pine [Pinus sylvestris (L.)] woods were determined in transverse directions for moisture conditions from oven-dry to 22 percent at a room temperature of 22 to 24 °C. Results indicate that the behaviors of thermal conductivity and dielectric parameters with moisture content and structural directions were similar. In general, the properties increased within the range studied with increasing moisture content. The radial values were similar to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…As a consequence, the treated wood has a lower water affinity (Herrera et al 2014). This indicates that water uptake and absorption in wood slow down, so the amount of water in the wood decreases (Hill 2006;Gu and Hunt 2007;Sahin Kol 2009;Sahin Kol and Sefil 2011). The k-value of water is much higher than wood, so the k-value tends to increase as EMC increases or decreases as EMC decreases.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, the treated wood has a lower water affinity (Herrera et al 2014). This indicates that water uptake and absorption in wood slow down, so the amount of water in the wood decreases (Hill 2006;Gu and Hunt 2007;Sahin Kol 2009;Sahin Kol and Sefil 2011). The k-value of water is much higher than wood, so the k-value tends to increase as EMC increases or decreases as EMC decreases.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the weight gain results for control WS, WS-LG, WS-LG/TO, WS-LG/EG, and WS-LG/TO/EG composites, it can be concluded that thermal conductivity at 23 • C/50% for all compositions is almost unaltered due to the hygroscopic nature of control WS and the increased hydrophobicity of LG, LG/TO, LG/EG, and LG/TO/EG coated WS composites. In other words, as control WS is more prone to moisture, its thermal conductivity increases, as Kol [32] and Troppová et al [33] revealed that the thermal conductivity of pine wood significantly increases under different moisture contents. The moisture content in wood or wood particles increases water molecules within the wood or wood particles matrix.…”
Section: Constant Coefficients In Equationsmentioning
confidence: 91%
“…The wood powder comprises cellulose, lignin, hemicellulose, and other substances that respond differently to electric field frequency. When the moisture content of wood powder approaches 0, under the force of an external electric field, the direction of the electric moment of the internal dipoles of wood powder shifts towards the direction of the external electric field, arranged according to the direction of the electric field, resulting in the relative displacement of the electric moment, leading to directional polarization (Kol 2009). However, as the frequency increases, the polar molecules inside the wood powder are quickly polarized.…”
Section: Infrared Spectroscopy Measurement Analysismentioning
confidence: 99%